COVID-19-Related Daily Stress Processes in College-Aged Adults: Examining the Role of Depressive Symptom Severity - Greaney, Jody L.; Darling, Ashley M.; Turner, Jennifer R.; Saunders, Erika F. H.; Almeida, David M.; Mogle, Jacqueline (Frontiers in Psychology, 2021)
Exposure to daily stressors specific to the COVID-19 pandemic (e.g., threat of infection) is associated with emotional distress, heightened stress reactivity, and increased depressive symptomology. Herein, we examined whether current depressive symptomology modulates the association between COVID-19-related daily stressor exposure and negative affective reactivity in young, otherwise healthy, college-adults remains unclear. Fifty-eight adults (21 men; 22±3 yrs) completed a daily web-based interview for 8 consecutive days to assess COVID-19-related daily stress exposure and emotional responsiveness (Sept-Nov 2020). Depressive symptom severity was assessed using the Patient Health Questionnaire-9 (PHQ-9), and a score of ≥10 (range: 0-27) was used to define adults with a depressive episode (n=20). Participants reported at least one COVID-19-related stressor on 35.8% of interview days. Depressive symptomology did not predict the likelihood of exposure to a COVID-19-related stressor (p=0.46; OR = 1.52; 95% CI: 0.492-4.718). However, negative affect was greater on days with an exposure to any COVID-19-specific daily stressor in adults with moderate-to-severe depressive symptoms (b=0.28, SE=0.093, p=0.003) but not in those without (b=0.009, SE=0.074, p=0.90), such that negative affective reactivity to COVID-19-related stressors was amplified in adults with a current depressive episode (p=0.019). Depressive symptomology did not moderate positive affective reactivity (p=0.686). Taken together, these data suggest that exposure to daily stressors related to COVID-19 further worsens negative affect in adults with a current depressive episode, potentially rendering them more susceptible to adverse mental health outcomes during the pandemic.